SISTEM MONITORING DAN PEREKAMAN KEHADIRAN MENGAJAR DOSEN BERBASIS RFId DAN DATABASE UNTUK PENINGKATAN MUTU PENGAJARAN - Yul Hendra; Ely Nuryani (Program Studi Sistem Informasi, Universitas Banten Jaya, 2021)
In this study there are 3 topics of discussion, namely the problem of monitoring the teaching presence of lecturers, recording data on the use of the room into a database that can be accessed by an online application in realtime. The methodology used in this study is the prototype method which has the following stages: 1. Identification of needs, 2. Building Prototype, 3. Coding, 4. Testing and Evaluation of Prototype ,. The system is created using the application of Radio Frequency Identification (RFId) technology, the PHP programming language and MySQL as the software and database. RFId technology is used as an input device when lecturers enter using the RFId Card. The RFId Card is used by lecturers for attendance that will be automatically recorded into the database along with the room, day and hour data. This system can be accessed by users through a web-based application to facilitate the Academic Section, the Financial Section and the Head of the Study Program and the leadership to monitor and track the number of lecturers' teaching attendance in class. The result is a monitoring and recording system for teaching attendance based on RFId lecturers and this database helps the Academic Section, the Finance Section and the Head of the Study Program and the leadership in monitoring and overseeing lecturer attendance.